Analysis Readiness of South Kalimantan Swimming Athletes in The Face of National Championships - Lazuardy Akbar Fauzan; Edwin Wahyu Dirgantoro; Ihip Ihip; Sofia Monalisa; Muhammad Fauzi Rahman (Universitas PGRI Palembang, 2022)
Athlete achievement can be measured from the readiness of physical, technical, mental, and strategic aspects. Swimming is a prestigious sport so its achievements are highly expected. The purpose of this research is to know the readiness of swimming athletes pengprov PRSI South Kalimantan in participating in the national championship. This study is a descriptive quantative study. The population in this study was a national swimming athlete pengprov South Kalimantan which amounted to 17 people. The sampling technique used is total sampling. The data analysis technique used is descriptive statistical analysis. Based on the results of research analysis of physical readiness and engineering, South Kalimantan athletes obtained excellent results. But there are only 2 and 3 athletes who fall into the national category.